Acute Diffuse Renal Tubulopathy in a Patient With Lung Cancer: A Case Report - Tseng, Po-Jung; Yan, Ming-Tso (Frontiers in Medicine, 2021)
Immune checkpoints inhibitors (ICPIs), as either a frontline or adjuvant therapy, showed favorable outcomes among diverse malignancies. Immune-related adverse events (IRAEs) are increasingly encountered, but the kidneys are rarely affected. A 67-year-old man with stage IV squamous cell carcinoma of the lung presented with acute kidney injury and hypercalcemia secondary to bone metastasis. After an aggressive saline infusion and subcutaneous denosumab 60mg administration, his renal function and serum calcium level were recovered on day 4. Due to his intolerance to chemotherapy, immunotherapy with a monoclonal antibody targeting programmed cell death protein-1 (PD-1), pembrolizumab 2mg/kg, was used on day 4. On day 11, polyuria, non-albumin dominant proteinuria, and severe deficiencies of electrolytes (potassium 2.5 mmol/L, calcium 5.5 mg/dL, magnesium 1.3 mg/dL, and phosphate 1.5 mg/dL) along with concomitant renal wasting were developed acutely. Except for postponing the next pembrolizumab, prednisolone at 1 mg/kg/day was given on day 13. On day 27, his polyuria subsided and urine protein loss resolved. Serum levels of potassium, phosphate, calcium, and magnesium all returned within the reference range. This case highlighted that renal IRAEs, even though uncommon, could be severe and potentially life-threatening if left unrecognized and untreated. Early recognition of renal IRAEs and prompt withdrawal of ICPIs may result in lower renal morbidity.